Leadership of urban digital innovation for public value: A competency framework - Viviana Bastidas; Kwadwo Oti‐Sarpong; Timea Nochta; Li Wan; Junqing Tang; Jennifer Schooling (IET Smart Cities, 2024)
Abstract Leading digital innovation projects in smart cities requires the right human resources with the right set of competencies. Such requirement is challenging because city managers and built environment professionals are traditionally trained and work in disciplinary and professional silos. This results in a lack of knowledge, abilities, and tools to produce optimal outcomes for communities across multiple sectors. Guided by a socio‐technical and multidisciplinary approach, the DC2‐CF framework is proposed to help urban planners identify, develop and expand the competencies they need to effectively steer responsible digital innovation and ensure public value creation. The DC2‐CF proposes a digital innovation process model to facilitate the delivery of successful urban digital innovation projects based on the lessons learned from working with city digital leaders. In addition, the DC2‐CF provides a delivery structure which identifies specific tasks, competencies, and roles necessary to enable the use off the innovation process model in practice and break down the professional silos currently existing in cities. The framework is envisioned to assist city planners in fostering leadership capacity in local authorities and the private sector in digital city development, contributing to enhancing collaborative working and effective public value creation.